5x+3(x-6)=7x+13 After expanding the brackets the equation becomes

5x + 3x -18 = 7x +13 the numbers containing x need to be moved on one side of the “=” sign and the resto of the numbers moved on the other side.

8x-7x= 13+18

x=31

**Equation with brackets – Example 2 **

4(x+5)-3(x-3)=2(x+5)

4x+20+3x+9=2x+30 After expanding the brackets, the equation becomes

4x-3x-2x=30-29 the numbers containing x need to be moved on one side of the “=” sign and the resto of the numbers moved on the other side of the “=” sign

-x=1 multiply by (-) to change the signs

x=-1

**Equation with brackets – Example 3**

5(x+2)+4(x+2)=3(x+8)+12

5x+10+4x+8=3x+24+12 After expanding the brackets the equation becomes

9x+18=3x+36 the numbers containing x need to be moved on one side of the “=” sign and the resto of the numbers moved on the other side of the “=” sign

9x-3x=36+18

6x=18

x=3